Butterflies in tropical dry forest fragment at Montes of Maria (Colombia). (2018)
The richness of diurnal butterflies in the Montes de Maria (Serranía de Coraza) was characterized using linear transects of 600 m. long. Inside each transects eight circular plots of 15 m of radius were established. To collected butterflies, we used entomological network and Van Someren Rydon traps. To compare the composition, abundance and uniformity of the species in each transect and to establish if the samples were significant, range-abundance curves were performed. In addition, to calculated the expected number of species curve of rarefaction and extrapolation-interpolation were made. In total, 301 individuals were collected belongs to 4 families, 13 subfamilies, 22 tribes, 44 genera and 55 species. Nymphalidae have the highest abundance  (235) and richness (37), while Biblidinae (120 individuals) and Hamadryas februa (56 individuals) were more abundant subfamily and species. Results suggest that tropical dry forests of Coraza, despite the anthropic impact, have a great diversity butterflies’ species. Herein we show the importance of following studying the butterfly composition and diversity that allows, not only know the structure of these communities, also to increase the knowledge inside tropical dry forest entomofauna of Serrania Coraza reserve.